Preparation method and application of molecularly imprinted ionic gel adsorbent
By preparing a chitosan/cellulose molecularly imprinted ionogel adsorbent, the problem of insufficient selectivity of existing adsorbents for dibenzothiophene sulfides was solved, achieving efficient adsorption and resource recovery. It is suitable for selective adsorption of dibenzothiophene sulfides in fuel oil and recovery of high-value chemicals.
Patent Information
- Application Number
- CN202510966790.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-14
- Publication Date
- 2025-10-31
AI Technical Summary
Existing adsorbents have insufficient selective adsorption capacity for dibenzothiophene sulfides, which increases the difficulty of hydrodesulfurization. Furthermore, traditional synthesis routes are cumbersome and produce many byproducts, making it difficult to achieve diesel sulfur content standards and recover high-value chemicals.
Chitosan/cellulose molecularly imprinted ionogel adsorbents were prepared using a sol-gel coupled freeze-drying method, with imidazole ionic liquids used as crosslinking agents. The preparation process was green and mild, and a stable gel network was formed by using the hydroxyl and amino groups on the chitosan and cellulose segments as imprinting sites.
It achieves highly selective adsorption of dibenzothiophene sulfides with high adsorption capacity and good structural stability, making it suitable for industrial applications, reducing production costs, and expanding the application of biomass molecularly imprinted ion gels in the efficient selective recognition and resource recovery of fuel oil.
Smart Images

Figure CN120861002A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of preparation of molecularly imprinted materials and resource-based separation and recovery of dibenzothiophene sulfides in fuel oil, and relates to a method for preparing and applying a molecularly imprinted ion gel (ILs-MIP) adsorbent. Background Technology
[0002] Diesel fuel is an important energy product widely used in transportation, shipping, engines, and other related applications. Crude diesel fuel has a high sulfur content, and the sulfur oxides produced by the combustion of sulfides cause serious pollution to the environment. Desulfurization is a crucial step in achieving "oil conversion." Dibenzothiophene (DBT) and its derivatives account for approximately 70% of the total sulfide content in diesel fuel, making them the primary targets for removal. Currently, the widely used industrial hydrodesulfurization technology can effectively remove sulfides such as mercaptans and thioethers from crude diesel fuel. However, due to the stable structure and large steric hindrance of DBT-type aromatic sulfides, hydrodesulfurization is difficult. To achieve the China VI standard (sulfur content <10 ppm) for diesel fuel sulfur content, it is necessary to increase the hydrogen and energy consumption of existing hydrotreating processes.
[0003] On the other hand, DBT and its derivatives have great economic value as organic synthesis intermediates for pharmaceuticals, dyes, conductive materials, etc. For example, benzo[1,2-b:5,4-b']bis[1]benzothiophene (BBBT) based on the DBT structure is a potential raw material for the synthesis of thin film transistor materials. At present, DBT is mainly obtained by chemical synthesis methods such as CS and CC cyclization. Although the synthetic route is highly designable, the reaction steps are cumbersome and there are many by-products, which makes purification difficult.
[0004] Therefore, if solid adsorbents can be used to selectively and non-destructively separate DBT from diesel fuel, not only can the sulfur content of diesel fuel be reduced and its quality improved, but the desulfurization products can also be recovered as high-value chemicals. Traditional adsorbents mainly include metal oxides, molecular sieves, metal-organic frameworks, and carbon materials. However, these adsorbents lack specific designs for DBT sulfides in terms of configuration correspondence and mechanism of action, resulting in insufficient selective adsorption capacity for DBT sulfides. Summary of the Invention
[0005] To address the aforementioned technical problems, the present invention aims to provide a molecularly imprinted ion gel adsorbent with high recognition selectivity, which can be used for the selective adsorption, separation, and resource recovery of DBT-type sulfides in fuel oil.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] A method for preparing a molecularly imprinted ionogel adsorbent includes the following steps:
[0008] Chitosan (CS) and cellulose (CE) were added sequentially to an acetic acid solution and stirred until homogeneous. Then, an acetonitrile solution of dibenzothiophene sulfides was added dropwise, followed by a methanol solution of imidazole ionic liquids under stirring. After gelation at a certain temperature for a period of time, the resulting wet gel was freeze-dried. Subsequently, the gel was eluted several times with a mixed solvent of methanol and acetic acid until no signal peak of DBT sulfides was detected in the gas chromatograph. After freeze-drying again, chitosan / cellulose molecularly imprinted ionogel (ILs-MIP) adsorbent was obtained.
[0009] As a control, a non-molecularly imprinted ionogel (ILs-NIP) adsorbent was prepared by following the above procedures without the addition of DBT.
[0010] Preferably, in the above steps, the ratio of chitosan, cellulose, and acetic acid solution is 0.1–0.2 g: 0.1–0.2 g: 3–15 mL, and the volume concentration of the acetic acid solution is 1%.
[0011] Preferably, in the above steps, the dibenzothiophene sulfides include DBT and its derivatives, 4-methyldibenzothiophene 4-MDBT and its derivatives, or 4,6-dimethyldibenzothiophene 4,6-DMDBT and its derivatives.
[0012] Preferably, in the above steps, the acetonitrile solution of dibenzothiophene sulfide refers to a mixture of dibenzothiophene sulfide and acetonitrile, wherein the ratio of chitosan, cellulose, dibenzothiophene sulfide and acetonitrile is 0.1-0.2g: 0.1-0.2g: 6-40mg: 2-7mL.
[0013] Preferably, in the above steps, the imidazole ionic liquid includes 1-octyl-3-methylimidazolium chloride [Omim][Cl], 1-dodecane-3-methylimidazolium chloride [Domim][Cl], 1-octyl-3-methylimidazolium hexafluorophosphate [Omim][PF6], 1-dodecane-3-methylimidazolium hexafluorophosphate [Domim][PF6], 1-butyl-dimethylimidazolium acetate [Bmim][OAc], or 1-octyl-dimethylimidazolium acetate [Omim][OAc].
[0014] Preferably, in the above steps, the methanol solution of the imidazole ionic liquid refers to a mixture of imidazole ionic liquid and methanol, wherein the ratio of chitosan, imidazole ionic liquid and methanol is 0.1-0.2 mg: 1-4 g: 2-8 mL.
[0015] Preferably, in the above steps, the conditions for gelation are: gelation temperature 30-50℃ and gelation time 8-16h.
[0016] Preferably, in the above steps, the freeze-drying conditions are: freeze-drying temperature -50 to -40°C, and freeze-drying time 12 to 36 hours.
[0017] The molecularly imprinted ion gel adsorbent prepared in this invention is used for the selective adsorption, separation, and resource recovery of dibenzothiophene sulfides in fuel oil.
[0018] Compared with the prior art, the present invention has the following significant advantages:
[0019] (1) This invention prepares chitosan / cellulose molecularly imprinted ion gel (ILs-MIP) adsorbent by sol-gel coupling freeze drying method, using imidazole ion liquids instead of traditional glutaraldehyde or epichlorohydrin crosslinking agents, making the reaction process greener and the conditions milder.
[0020] (2) The relative selectivity coefficients of the ILs-MIP prepared in this invention for the interfering substances thiophene (T) and 4,6-dimethyldibenzothiophene (4,6-DMDBT) are 0.89 and 1.02, respectively. Moreover, the adsorption capacity of ILs-MIP for DBT (27.92±0.85mg / g) is significantly higher than that of chitosan non-imprinted sponge (ILs-NIP; 20.83±0.37mg / g), indicating that ILs-MIP has high recognition selectivity for DBT template molecules and can achieve efficient and selective adsorption of high-value DBT in fuel systems.
[0021] (3) The ILs-MIP prepared in this invention still maintains an adsorption capacity of 27.33±0.43mg / g after six cycles of regeneration, which has good structural stability, improves recycling rate and saves production costs.
[0022] (4) The ILs-MIP molecularly imprinted ion gel prepared by the present invention has an integral structure. Compared with traditional powder adsorbents, this integral adsorbent is easy to separate and recover from fuel oil and is suitable for industrial applications.
[0023] (5) In this invention, the hydroxyl and amino groups on the chitosan and cellulose segments can serve as imprinting sites. At the same time, cellulose can form a stable gel network with chitosan in an ionic liquid medium through hydrogen bonds, which significantly improves mechanical strength compared with a single chitosan gel.
[0024] (6) Currently, chitosan ionic liquid gel adsorbents have been widely used in the removal of pollutants from water bodies, but their application in the recovery of sulfur resources from fuel oil is still in the exploratory stage. This invention expands the application of biomass molecularly imprinted ionic gel adsorbents in the efficient and selective identification and resource recovery of high-value-added sulfides in fuel oil. Attached Figure Description
[0025] Figure 1Scanning and transmission electron microscopy images of the ILs-MIP prepared in Example 1 of this invention.
[0026] Figure 2 The infrared spectra of ILs-MIP prepared in Example 1 of this invention before and after adsorption of DBT are shown.
[0027] Figure 3 The results show the compressive stress test and adsorption capacity before and after compression of the ILs-MIP prepared in Example 1 of this invention.
[0028] Figure 4 The graph shows the change in adsorption capacity of ILs-MIP prepared in Example 1 of this invention over time.
[0029] Figure 5 The selective adsorption capacity of the ILs-MIP prepared in Example 1 of this invention for different aromatic compounds is shown.
[0030] Figure 6 The results of the cyclic stability analysis of the ILs-MIP prepared in Example 1 of this invention are shown. Detailed Implementation
[0031] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0032] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0033] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0034] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0035] Example 1:
[0036] 120 mg of chitosan and 120 mg of cellulose were completely dissolved in 6 mL of 1% (v / v) acetic acid solution. After stirring, 4 mL of DBT (13.7 mg) acetonitrile solution was added dropwise, followed by 4 mL of [Bmim][OAc] (2 g) methanol solution with stirring. The mixture was gelled at 40 °C for 12 h and then freeze-dried at -45 °C for 24 h. Subsequently, the mixture was eluted several times with a mixed solvent of methanol and formic acid until no signal peak of DBT-like sulfides was detected in gas chromatography. After freeze-drying again, chitosan / cellulose molecularly imprinted ionogel (ILs-MIP) adsorbent was obtained.
[0037] Example 2:
[0038] 100 mg chitosan and 100 mg cellulose were completely dissolved in 3 mL of 1% (v / v) acetic acid solution. After stirring, 2 mL of LDBT (7 mg) acetonitrile solution was added dropwise, followed by 2 mL of [Bmim][OAc] (1 g) methanol solution with stirring. The mixture was gelled at 30 °C for 8 h and then freeze-dried at -50 °C for 12 h. Subsequently, the mixture was eluted several times with a mixed solvent of methanol and formic acid until no signal peak of DBT-like sulfides was detected in gas chromatography. After freeze-drying again, chitosan / cellulose molecularly imprinted ionogel (ILs-MIP) adsorbent was obtained.
[0039] Example 3:
[0040] 200 mg chitosan and 200 mg cellulose were completely dissolved in 15 mL of 1% (v / v) acetic acid solution. After stirring, 7 mL of DBT (40 mg) acetonitrile solution was added dropwise, followed by 8 mL of [Domim][PF6] (4 g) methanol solution under stirring. The mixture was gelled at 50 °C for 16 h and then freeze-dried at -40 °C for 36 h. Subsequently, the mixture was eluted several times with a mixed solvent of methanol and formic acid until no signal peak of DBT-like sulfides was detected in gas chromatography. After freeze-drying again, chitosan / cellulose molecularly imprinted ionogel (ILs-MIP) adsorbent was obtained.
[0041] Example 4:
[0042] 120 mg of chitosan and 120 mg of cellulose were completely dissolved in 6 mL of 1% (v / v) acetic acid solution. After stirring, 4 mL of 6 mg of DBT solution was added dropwise, followed by 4 mL of 2 g of [Omim][OAc] methanol solution while stirring. The mixture was gelled at 40 °C for 12 h and then freeze-dried at -45 °C for 24 h. Subsequently, the mixture was eluted several times with a mixed solvent of methanol and formic acid until no signal peak of DBT-like sulfides was detected in gas chromatography. After freeze-drying again, chitosan / cellulose molecularly imprinted ionogel (ILs-MIP) adsorbent was obtained.
[0043] Example 5:
[0044] 120 mg of chitosan and 120 mg of cellulose were completely dissolved in 6 mL of 1% (v / v) acetic acid solution. After stirring, 4 mL of 4,6-DMDBT (16 mg) acetonitrile solution was added dropwise. Then, 4 mL of [Omim][Cl] (2 g) methanol solution was added while stirring. The mixture was gelled at 40 °C for 12 h and then freeze-dried at -45 °C for 24 h. Subsequently, the mixture was eluted several times with a mixed solvent of methanol and formic acid until no signal peak of DBT-like sulfides was detected in gas chromatography. After freeze-drying again, chitosan / cellulose molecularly imprinted ionogel (ILs-MIP) adsorbent was obtained.
[0045] Application example:
[0046] Taking the molecularly imprinted ionogel adsorbent prepared in Example 1 as an example, the adsorption activity of the ILs-MIP prepared in Example 1 was evaluated; with DBT as the adsorbent, the adsorption capacity of ILs-MIP for DBT was determined.
[0047] The specific steps are as follows:
[0048] Simulated diesel fuel containing a single sulfur compound was prepared using n-octane as a solvent. Different masses of DBT were dissolved in n-octane, and a certain amount of n-tetradecane was added as an internal standard to prepare simulated diesel fuel with DBT contents of 100, 200, 300, 400, 500 mg / L and 1000 mg / L.
[0049] Measure 20 mL of each of the above-mentioned DBT solutions of different concentrations and transfer them to 50 mL Erlenmeyer flasks. Add 50 mg of the prepared molecularly imprinted ionogel ILs-MIP to the Erlenmeyer flasks. Transfer the Erlenmeyer flasks to a SHA-B dual-function constant temperature water bath shaker and set the rotation speed to 130 rpm. Maintain the shaker at 25℃, 35℃, and 45℃ for 6 h until adsorption equilibrium is reached. Collect the supernatant and measure the remaining sulfur content using an Agilent gas chromatograph-7890A.
[0050] The Agilent-7890A gas chromatograph was set with the following parameters: an HP-5 column was used for separation, and a flame ionization detector was used for detection; a mixture of nitrogen, hydrogen, and oxygen was used as the gas source, with flow rates of 30 mL / min (H2), 400 mL / min (O2), and 25 mL / min (N2), respectively; the gas chromatograph was programmed with a temperature ramp of 5 min and a retention time of 3 min. The peak area at 6.375 min was integrated to obtain the remaining DBT content, and the adsorption capacity of the molecularly imprinted ionogel adsorbent ILs-MIP for DBT over 6 h was calculated.
[0051] Figure 1 The images show scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the ILs-MIP prepared in Example 1 of this invention. As can be seen from the SEM images, the prepared ILs-MIP exhibits a sheet structure. Furthermore, it can be clearly seen from the TEM images that the sheet surface of the ILs-MIP is not smooth and flat, but rather exhibits a wrinkled grid structure, which is beneficial for the adsorption of DBT template molecules in hydrotreated diesel.
[0052] Figure 2 The figures show the infrared spectra of ILs-MIP prepared in Example 1 of this invention before and after DBT adsorption. As can be seen from the figures, compared with the infrared spectrum of ILs-MIP, after DBT adsorption, the stretching vibration peak attributable to the imidazole ring in ILs-MIP decreased from 1561 cm⁻¹ before adsorption. -1 Slightly offset to 1554cm -1 A redshift occurred, presumably due to charge transfer between the sulfur atom on the thiophene ring of the DBT molecule and the imidazole ring of ILs-MIP.
[0053] Figure 3 The figure shows the compressive stress test results of the ILs-MIP prepared in Example 1 of this invention. As can be seen from the figure, the ILs-MIP begins to deform with increasing pressure. Without damage to its overall structure, the maximum stress that the ILs-MIP can withstand is approximately 0.9 × 10⁻⁶. -3 MPa was applied, and the deformation height was 50% of the original height. Then the applied pressure was removed to test the material's resilience. As can be seen from the compressive stress closed curve, the material eventually recovered to its original height, confirming that ILs-MIP has excellent compressive strength and resilience. Figure 3 The inset is a comparison of the adsorption performance of ILs-MIP prepared in Example 1 of this invention before and after compression. As can be seen from the figure, the adsorption capacity of ILs-MIP for DBT after compression did not change significantly compared with that before compression, indicating that the structure of ILs-MIP was not destroyed after compression and still maintained good adsorption performance.
[0054] Figure 4The graph shows the adsorption capacity of ILs-MIP prepared in Example 1 of this invention as a function of time. As can be seen from the graph, within 0 to 600 min, ILs-MIP exhibits rapid adsorption of DBT with increasing adsorption time. After 600 min, the adsorption reaches equilibrium, and the equilibrium adsorption capacity is 27.92±0.85 mg / g, which is higher than that of ILs-NIP (20.83±0.37 mg / g).
[0055] Figure 5 The figure shows the selective adsorption capacity of ILs-MIP prepared in Example 1 of this invention for different aromatic compounds. As can be seen from the figure, when T and 4,6-DMDBT coexist, the adsorption capacity of ILs-MIP for DBT (19.35 mg / g) is significantly higher than that for T and 4,6-DMDBT. This indicates that in the multi-component mixed solution, ILs-MIP exhibits selective adsorption of DBT, and the adsorption capacity for DBT is significantly higher than that of ILs-NIP.
[0056] Figure 6 The figure shows the cycle stability analysis results of the ILs-MIP prepared in Example 1 of this invention. As can be seen from the figure, the prepared ILs-MIP still maintains a stable adsorption capacity for DBT (27.33±0.43mg / g) after six cycles, which confirms that ILs-MIP has good stability and cycle regeneration performance.
[0057] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Therefore, although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the present invention. All technical solutions and improvements that do not depart from the spirit and scope of the present invention should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing a molecularly imprinted ionogel adsorbent, characterized in that, The steps are as follows: Chitosan (CS) and cellulose (CE) were added sequentially to an acetic acid solution and stirred until homogeneous. Then, an acetonitrile solution of dibenzothiophene sulfide was added dropwise. A methanol solution of imidazole ionic liquid was added while stirring. After gelation at a certain temperature for a period of time, the resulting wet gel was freeze-dried. Subsequently, the mixture was soaked and eluted several times with a mixed solvent of methanol and acetic acid until no signal peak of DBT-type sulfides could be detected in gas chromatography. After freeze-drying again, chitosan / cellulose molecularly imprinted ionogel ILs-MIP adsorbent was obtained.
2. The method for preparing the molecularly imprinted ionogel adsorbent according to claim 1, characterized in that, The ratio of chitosan, cellulose, and acetic acid solution is 0.1–0.2 g : 0.1–0.2 g : 3–15 mL, and the volume concentration of the acetic acid solution is 1%.
3. The method for preparing the molecularly imprinted ionogel adsorbent according to claim 1, characterized in that, Dibenzothiophene sulfides include DBT and its derivatives, 4-methyldibenzothiophene 4-MDBT and its derivatives, or 4,6-dimethyldibenzothiophene 4,6-DMDBT and its derivatives.
4. The method for preparing the molecularly imprinted ionogel adsorbent according to claim 1, characterized in that, The acetonitrile solution of dibenzothiophene sulfides refers to a mixture of dibenzothiophene sulfides and acetonitrile, wherein the ratio of chitosan, cellulose, dibenzothiophene sulfides and acetonitrile is 0.1-0.2g: 0.1-0.2g: 6-40mg: 2-7mL.
5. The method for preparing the molecularly imprinted ionogel adsorbent according to claim 1, characterized in that, Imidazole ionic liquids include 1-octyl-3-methylimidazolium chloride [Omim][Cl], 1-dodecane-3-methylimidazolium chloride [Domim][Cl], 1-octyl-3-methylimidazolium hexafluorophosphate [Omim][PF6], 1-dodecane-3-methylimidazolium hexafluorophosphate [Domim][PF6], 1-butyl-dimethylimidazolium acetate [Bmim][OAc], or 1-octyl-dimethylimidazolium acetate [Omim][OAc].
6. The method for preparing the molecularly imprinted ionogel adsorbent according to claim 1, characterized in that, A methanol solution of imidazole ionic liquids refers to a mixture of imidazole ionic liquids and methanol, wherein the ratio of chitosan, imidazole ionic liquids and methanol is 0.1–0.2 mg: 1–4 g: 2–8 mL.
7. The method for preparing the molecularly imprinted ionogel adsorbent according to claim 1, characterized in that, The conditions for gelation are: gelation temperature 30–50℃, gelation time 8–16 h.
8. The method for preparing the molecularly imprinted ionogel adsorbent according to claim 1, characterized in that, The freeze-drying conditions are: freeze-drying temperature -50 to -40℃, freeze-drying time 12 to 36 hours.
9. The molecularly imprinted ionogel adsorbent prepared by the preparation method according to any one of claims 1 to 8 is used for the efficient and selective identification and resource recovery of high-value-added sulfides in fuel oil.